2020
DOI: 10.1097/md.0000000000019275
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative imatinib treatment in patients with locally advanced and metastatic/recurrent gastrointestinal stromal tumors

Abstract: The advent of imatinib mesylate (IM) has dramatically revolutionized the prognosis of advanced and metastatic/recurrent gastrointestinal stromal tumors (GISTs). The objective of this retrospective study is to investigate the safety and efficacy of combination of surgery following IM treatment in the management of advanced and metastatic/recurrent GISTs. We further explore the long-term clinical outcomes in these who underwent therapy of preoperative IM. Eligible patients with GISTs before the onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Further studies showed that IM used as a preoperative adjuvant therapy in DFSP lead to median tumor volume shrinkages from 20% to 31.5% [ 39 , 107 , 113 , 114 ], which transformed very large, unresectable tumors into resectable ones. Wang et al reported four of 10 patients with primarily unresectable DFSP received complete surgical resection following IM treatment [ 38 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Further studies showed that IM used as a preoperative adjuvant therapy in DFSP lead to median tumor volume shrinkages from 20% to 31.5% [ 39 , 107 , 113 , 114 ], which transformed very large, unresectable tumors into resectable ones. Wang et al reported four of 10 patients with primarily unresectable DFSP received complete surgical resection following IM treatment [ 38 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Follow-up imaging should be done to evaluate for treatment response. Wang et al[ 80 ] did a single center analysis in which patients with advanced and metastatic/recurrent GISTs were given imatinib mesylate for a median period of 8.2 mo preoperatively and tumor shrinkage was observed in almost 30% of cases. If the response is good and the disease remains stable, continue imatinib or avapritinib, and surgery consult should be done to consider resection.…”
Section: Treatment Of Unresectable Metastatic or Recurrent Gistsmentioning
confidence: 99%
“…A total of 10 studies [25][26][27][28][29][30][31][32][33][34] including 1119 patients (361 patients in the surgery group and 758 patients in the no surgery group) met the eligibility criteria and were included in the nal analysis (Figure 1). Manual searches of the references lists of the included studies did not yield any further studies.…”
Section: Study Selection and Qualitymentioning
confidence: 99%
“…One randomized control trial 28 and 4 retrospective studies 27,30,33,34 with scores of six or higher on the NOS were included in the sensitivity analysis. The results related to OS and PFS did not changed signi cantly in the sensitivity analysis (shown in supplementary material Figure S1 and Figure S2).…”
Section: Sensitivity Analysis and Publication Biasmentioning
confidence: 99%